Metode Hafalan dalam Pembelajaran Naḥwu di Madrasah Diniyah Kyai Mojo, Tembelang, Jombang - Rusyadi, Muhammad Hilmi Bahar; Muassomah (Al-Ma‘rifah, 2020)
Many studies that discuss learning methods naḥwu, there is no method that can be accurate to be applied to all Madrasahs. Madrasah Diniyah Kyai Mojo, Tembelang, Jombang, is one of the Madrasahs that applies the rote method to improve the quality of understanding naḥwu. The purpose of this study is to find out how the application of memorization methods in Madrasah Diniyah Kyai Mojo, Tembelang, Jombang, in improving the quality of students’ understanding of naḥwu. This study uses descriptive qualitative, and the instrument for collecting data using direct observation, and unstructured interviews. The results of this study indicate that the application of the memorization method in improving naḥwu in the Madrasah Kyai Mojo, Tembelang, Jombang consists of two stages, namely the preparation stage and the implementation and evaluation stages. The study concludes that the memorization method is very helpful in improving the quality of students’ understanding of naḥwu, even though the level of understanding is still at the level of translating and interpreting and has not yet reached the stage of extrapolating (estimating). his study suggests teachers be creative in using learning methods by paying attention to situations and conditions so that learning is not monotonous by using one method.